PENGEMBANGAN BAHAN AJAR PAI BERBASIS MULTIKULTURAL DI SMP NEGERI 17 MEDAN - Sarfika Saragih, Ali Imran Sinaga, Mardianto (Pascasarjana UIN Sumatera Utara, 2018)
Abstract: This study attempts to (1) make and depelove of multicultural based teaching materials PAI aboutmatter tolerance and appreciate differences, (2) described a study results and response of students about that,(3) to know a results effective for that. Using method research and development (R & D), refers to Borg andGall models. Subject trial consisted of material experts, design experts, PAI teachers, students of class IX-3 atSchool, individual trials (3 students), small group trials (9 students), limited field trials (30 students). Dataabout a quality of development this collected by questionnaire. The results of the study indicates: (1) materialexpert validation includes aspects of eligibility content with an average of 87.5% with the criteria of “verygood” the feasibility aspect of presentation with an average of 80.35% with the criteria “good”, languageaspects 80.35% with the criteria “good”. (2) validation of design experts with an average of 83.62% with thecriteria of “good”. (3) the responses data PAI teacher with an average of 82.35% with the criteria of “good”,(4) individual trials with an average of 84.72% with “very good criteria, small group trials with an average of84.25 with the criteria of” very good “, limited field trials with an average of 95.83% with criteria for “verygood”. this proves that multicultural based PAI teaching materials development is appropriate for use inlearning matter Q.S. Al-Hujurat/49: 13 about tolerance and appreciate differences and hadiths related for thestudents of class IX-3 at Public Junior High School 17 Medan.Abstrak: Penelitian ini bertujuan untuk (1) mengembangkan dan menghasilkan Bahan Ajar PAI berbasis multikultural,(2) mendeskripsikan hasil belajar dan respon siswa terkait dengan Pengembangan Bahan Ajar PAI BerbasisMultikultural, (3) mengetahui hasil efektivitas Bahan Ajar PAI Berbasis Multikultural yang dikembangkan padamateri Toleransi dan Menghargai Perbedaan pada siswa kelas IX-3 SMP Negeri 17 Medan. Metode penelitianyang digunakan Research and Development (R&D) model Borg dan Gall. Subjek uji coba terdiri dari ahlimateri, ahli desain, guru PAI, dan siswa kelas IX-3, perlakuan uji coba yaitu uji coba perorangan (3 siswa), ujicoba kelompok kecil (9 siswa), uji coba lapangan terbatas (30 siswa). Data tentang kualitas produk pengembangandikumpulkan dengan angket. Hasil penelitian menunjukkan bahwa: (1) validasi ahli materi meliputi aspekkelayakan isi dengan rata-rata 87,5% dengan kriteria “Sangat Baik”, aspek kelayakan penyajian dengan ratarata80,35% dengan kriteria “Baik”, aspek bahasa 80,35% dengan kriteria “Baik”, (2) validasi ahli desaindengan rata-rata 83,62% dengan kriteria “Baik” (3) data tanggapan guru PAI dengan rata-rata 82,35% dengankriteria “Baik” (4) uji coba perorangan dengan rata-rata 84,72% dengan kriteria “Sangat Baik, uji cobakelompok kecil dengan rata-rata 84,25 dengan kriteria “Sangat Baik”, uji coba lapangan terbatas dengan ratarata95,83% dengan kriteria “Sangat Baik”. Hal ini membutikan bahwa pengembangan bahan ajar PAIberbasis multikultural layak digunakan pada pembelajaran materi Q.S. Al-Hujurat/49: 13 tentang Toleransidan Menghargai Perbedaan dan hadits terkait di kelas IX SMP Negeri 17 Medan.Kata kunci: Pengembangan Bahan Ajar, Pendidikan Agama Islam, Berbasis Multikultural